KEPEMIMPINAN PENDIDIKAN KRISTEN DI SMK SWASTA HKBP SIDIKALANG KABUPATEN DAIRI - Bryan King Hutagalung; Tetti Manullang (CV. Denasya Smart Publisher, 2024)
This research examines the importance of leadership in Christian education at the HKBP Sidikalang Private Vocational School, Dairi Regency. This book explores the practices and strategies used in fostering character development, moral values, and spirituality among students, while ensuring the integration of Christian values ​​into the curriculum and school activities. Through interviews, observations, and a literature review, this research underscores the important role of Christian educational leadership in establishing a holistic learning environment. Findings reveal the importance of spiritual guidance, character building, and community engagement facilitated by such leadership. The conclusion offers recommendations for strengthening spiritual development, improving curriculum integration, providing training for teachers, increasing parental involvement, and innovating extracurricular activities to promote Christian values. By implementing these suggestions, the effectiveness of Christian education leadership at HKBP Sidikalang Private Vocational School can be increased, thereby encouraging the growth of students who are morally upright and ready to have a positive impact on society.